INTERDISCIPLINARY APPROACH TO STUDYING SOCIAL HEALTH IN WOMEN IN THEIR REPRODUCTIVE AGE - Dinara D. Bairamkulova (Вестник Северо-Кавказского федерального университета, 2022)
The item dwells on the issue and the need to study social health in women in their reproductive age; there is an analysis into various approaches to under-standing the concept of health, as well as the concepts of women in reproductive age, social health, health in Medicine, health in Philosophy, Psychology, and Sociology